Effect of progesterone and pregnancy on the development of varicose veins - Lenković, Maja; Čabrijan, Leo; Gruber, Franjo, liječnik; Batinac, Tanja; Manestar Blažić, Teo; Stanić-Zgombić, Zrinka; Stašić, Adalbert (2009)
Summary: The aim of this study was to investigate the contribution of progesterone in the development of primary varicose veins on lower limbs during pregnancy. In 50 primiparae with varicose veins, serum progesterone level was quantitatively determined in the 14th week of pregnancy and results were compared with those obtained in a control group of 25 primiparae without visible varicose veins. The mean serum progesterone concentration recorded in pregnant women with dilated veins (159.9±15.8 nmol/L) was significantly higher as compared with the control group (159.9±15.8 nmol/L vs. 40.4±1.6 nmol/L; P<0.0001). These findings supported the role of hormonal factor in the development of varicose veins in women
Bibliografija: 21 jed
Keywords: Varikozne vene -- Trudnoća -- Progesteron